2022
DOI: 10.2147/ijgm.s389145
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Epidemiological Characters of Developmental Dysplasia of the Hip in Lianyungang: Based on Ultrasound Screening: A Retrospective Study

Abstract: Objective To explore the incidence and epidemiological characteristics of developmental dysplasia of hip (DDH) in Lianyungang and provide a basis for early detection, early diagnosis and early treatment. Methods Ultrasound screening was performed on aged 4–6 weeks to collect the incidence and epidemiological profiles of DDH. Graf hip ultrasound imaging was used for screening. DDH was diagnosed with a classification of ≥IIa − . R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Studies on the incidence of DDH using various physical examination and imaging methods show rates ranging from 0.5% to 1.5% 2. Dongsheng Zhu's study in China analyzed the results of 9803 infants and reported a DDH incidence rate of 1.19% [8]. Çekiç et al [9] used the Graf USG method to screen 1162 infants in the western Mediterranean region and found an incidence rate of 1.36%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the incidence of DDH using various physical examination and imaging methods show rates ranging from 0.5% to 1.5% 2. Dongsheng Zhu's study in China analyzed the results of 9803 infants and reported a DDH incidence rate of 1.19% [8]. Çekiç et al [9] used the Graf USG method to screen 1162 infants in the western Mediterranean region and found an incidence rate of 1.36%.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral challenges include medullary canal stenosis, excessive anterior tilt, and high diaphragm-diaphragm angle with epiphyseal mismatch. [ 4 ] Domestic data show that the incidence of this disease ranges from 1.1‰ to 3.8‰, [ 5 ] and the pathogenesis has not been clearly determined, and is now mostly considered to be related to genetic and mechanical factors in clinical practice. [ 6 , 7 ] At present, many patients are under-recognized for DDH and are admitted to the hospital with CroweIV DDH.…”
Section: Introductionmentioning
confidence: 99%